The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.athoracsur.2016.11.080
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Children’s Heart Surgery Data: A Cross-Disciplinary Approach to Codevelop a Website

Abstract: Risk-adjusted survival statistics after children's heart surgery are published annually in the United Kingdom. Interpreting these statistics is difficult, and better resources about how to interpret survival data are needed. Here we describe how a multidisciplinary team of mathematicians, psychologists, and a charity worked with parents of heart surgery children and other users to codevelop online resources to present survival outcomes. Early and ongoing involvement of users was crucial and considerably change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…It is also important to note that within the current methods for determining performance categories, most hospitals fall into the middle or “same-as-expected” category. Ongoing efforts are focused on exploring additional methods to continue to improve how performance data are conveyed to the public and other stakeholders [13]. …”
Section: Commentmentioning
confidence: 99%
“…It is also important to note that within the current methods for determining performance categories, most hospitals fall into the middle or “same-as-expected” category. Ongoing efforts are focused on exploring additional methods to continue to improve how performance data are conveyed to the public and other stakeholders [13]. …”
Section: Commentmentioning
confidence: 99%
“…Their group found that things like the use of ratios versus percentages, horizontal versus vertical orientation of graphics, and wording of text all had important effects on correct interpretation of the data. 30 Additional efforts are needed to improve these aspects of current reports across the US. Moving forward, further examination of the type of outcomes reported will also be important.…”
Section: Recommendationsmentioning
confidence: 99%
“…Public reporting in the realm of congenital heart surgery is not unique to the United States and was previously instituted in the United Kingdom. This issue of The Annals includes a series of three articles from the United Kingdom describing their recent work focused on advancing public reporting methods [8][9][10]. These efforts have centered on two critical aspects of public reporting: (1) improving case mix adjustment and (2) optimizing methods for conveying outcomes data with the public.…”
Section: For Related Articles See Pages 211 220 and 342mentioning
confidence: 99%
“…It has been shown previously that case mix can vary widely across congenital heart centers, including both the type and the frequency of different congenital heart defects treated, and patient comorbidities and risk factors such as genetic syndromes and noncardiac anomalies [10]. Thus, it is important to take differences in case mix into account in the characterization of a hospital's outcomes so as not to penalize those caring for a higher-risk patient population.…”
Section: For Related Articles See Pages 211 220 and 342mentioning
confidence: 99%